Theoretical and practical problems of optimization the long bone fractures osteosynthesis in patients with varying degrees of trauma severity. - Lapshyn, D. V.; Berezka, M. I. (Морфологія / Morphologia / Morfologìâ, 2016)
Background. Today the treatment of polytrauma pathologies is complicated by two major problems. Firstly, there is still no universally accepted injury and severity scale for patients with polytrauma, that makes it impossible to develop an objective prognosis and treatment outcomes for victims. Secondary, the universal surgical treatment in patients with long bone fractures in the polytrauma remains indeterminate, the best ways to be agreed stabilization of fractures, depending on the severity of the general condition of patients, location and character of the musculoskeletal system damage. Objective. Justification ways to improve the results of osteosynthesis in patients with multiple and associated fractures of long bones by optimizing treatment strategy based on scoring and severity of injuries. Methods. It was worked out case histories of 226 patients (160 men and 66 women) with combined trauma to determine the optimal scales. To support the optimal volume of osteosynthesis tactics for patients with multiple and associated long bones fractures based on scoring and severity of the injuries, it was analyzed the treatment results of 104 this category patients (75 men and 29 women). All patients were divided into main (43 persons) and the control group (61 persons) on the basis of one-step (main group) or two-step (control group) surgical treatment. Results. Mathematical and statistical analysis of the four most widespread rating and severity scales of the damage in polytrauma, gave the opportunity to determine two the most effective ones in terms of constructive and prognostic validity, informative and ease of use. In order to determine the advantages and disadvantages of one-step and two-step treatment schemes of multiple and associated long bone fractures in patients with injury severity by ISS 25-40 points and severity by VPH-SP 21-32 points, the treatment results were compared by author system of health and social criteria. Conclusion. It is proved that the optimal treatment strategy for victims with multiple and combined fractures of long bones is one-step, including all types of ex-fix osteosynthesis with reposition of bone fragments and closed intramedullary blocked nailing osteosynthesis.